Can the Remaining Coronal Tooth Structure Influence the Mechanical Behavior of Nonpost Full Crowns? - Pinto, Alana Barbosa Alves; Andrade, Guilherme Schmitt de; Abu Hasna, Amjad; Souza, Joyce Rodrigues de; Tribst, João Paulo Mendes; Borges, Alexandre Luiz Souto (European Journal of Dentistry, 2024)
Objectives This study investigated the impact of the remaining coronal tooth structure on the mechanical behavior of nonpost (NP) full crowns on endodontically treated maxillary central incisors.Materials and Methods Forty bovine incisors with NP and 2-mm of ferrule were divided into four groups based on the remaining structure: complete 2-mm ferrule (NP-2), absence of mesial and distal ferrule effect (NP-BL), absence of buccal and lingual ferrule effect (NP-MD), and no ferrule (NP-0). The specimens underwent a stepwise stress fatigue test until fracture occurred, and stress distribution was analyzed using in silico finite element analysis (FEA). Additionally, groups with endodontic posts (P) were simulated in the FEA.Results The results showed that the survival rates varied among the different groups under oblique loading. The NP-2 group exhibited the highest survival rate, with all samples enduring loads up to 200 N and some surviving up to 520 N. The NP-MD and NP-BL groups had lower survival rates, while the NP-0 group had the poorest survival rate. The predominant failure mode was a nonrepairable root fracture. FEA results indicated no significant difference between groups with and without posts. NP intraradicular restorations on nonweakened roots with a minimum height of 2mm and partial or total ferrule thickness of 1mm offer a promising treatment option.Conclusion A complete 2-mm ferrule was found to be the most favorable configuration for NP full crowns. However, maintaining the remaining tissue is crucial, as both combinations with preserved ferrule effect exhibited superior behavior in terms of fatigue and fracture load compared to the group with no ferrule. These findings contribute to understanding the mechanical considerations for NP full crowns and provide insights into treatment planning and design choices in restorative dentistry.
Keywords: crowns; endodontically treated incisors; fatigue; fracture resistance; finite element analysis.